2006
DOI: 10.4161/cc.5.16.2861
|View full text |Cite
|
Sign up to set email alerts
|

Itch/AIP4 Associates with and Promotes p63 Protein Degradation

Abstract: ABSTRACTp63, a protein related to the tumor suppressor p53, is a transcription factor that plays an important role in epidermal differentiation and limb development. The gene has two distinct promoters that allow the formation of proteins that either contain (TA) or lack (∆N) a transactivation domain. In addition, alternative splicing at the 3' end generates proteins with different C-termini, denoted α, β and γ for a total of six isoforms. ∆Np63α isoform is the main isoform expressed at all stages of developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 22 publications
2
76
0
Order By: Relevance
“…Increasing evidence suggests that protein ubiquitination and degradation have an important function for the p63 activity. [23][24][25]33 Two other WWP1 family members, Itch and Nedd4, have been previously reported to target p63 proteins for proteasomal degradation. 24,25 However, the expression levels of Itch in breast cancer are not altered 34 although the expression of Nedd4 has been found to be overexpressed in invasive bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that protein ubiquitination and degradation have an important function for the p63 activity. [23][24][25]33 Two other WWP1 family members, Itch and Nedd4, have been previously reported to target p63 proteins for proteasomal degradation. 24,25 However, the expression levels of Itch in breast cancer are not altered 34 although the expression of Nedd4 has been found to be overexpressed in invasive bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Suggesting that diminished ΔNp63α is associated with di erentiation of cervical squamous cancer, and might be also related with progression from super cial to invasive tumours. e regulation of ΔNp63α expression is involved in ubiquitin-proteasome degradation mediated by HECT domain family members such as ITCH and WWP1 [25][26][27][28], the transcriptional regulation of nuclear transcription factors, and the inhibition of protein translation by miR-203 [29]. Persistent infection with high-risk human papillomavirus (HR-HPV) is closely associated with cervical cancer [30], and HR-HPV can bind to their receptors speci cally expressed in cervical basal cells [31][32][33], the integration of HR-HPV DNA into host cells can disrupt normal cervical sqaumous di erentiation by altering several transcriptional factors to promote the initiation of the carcinogenic process [34][35][36][37][38], and their coding proteins,E6 and E7 contribute to disorganised layer formation and hyperplasia in organotypic cultures [35,39], us, HR-HPV infection probably contribute to ΔNp63α inactivation during tumourigenesis.…”
Section: © 2011 Cimmentioning
confidence: 99%
“…Recently, we have demonstrated that the homeodomain Dlx3 protein triggers proteasome-dependent Np63 degradation (Di Costanzo et al, 2009) whereas Np63 proteasomal degradation, in response to genotoxic stress, has been proposed to involve RACK1 (Li et al, 2009). Also, the E3 ubiquitin ligases NEDD4 and ITCH/AIP4 have both been found to be involved in the control of p63 steady state level (Rossi et al, 2006a;Rossi et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…p63 protein stability is regulated by protein modifications such as phosphorylation, ubiquitylation and sumoylation (Ghioni et al, 2005;Rossi et al, 2006a;Rossi et al, 2006b). Proteasomes and lysosomes have both been found to be involved in p63 protein degradation (Watson and Irwin, 2006).…”
Section: Introductionmentioning
confidence: 99%